PENGARUH DIMENSI-DIMENSI KEPERCAYAAN TERHADAP PERILAKU MILENIAL PADA - Lasmery Girsang; Michael Christian (Universitas Bunda Mulia, 2017)
Nowadays, traditional media to advertise is shifting to the online media. The millenias beccome the vital factor. Further, the technology and the habit to watch ads are important items on it. The habit of this group make online ads are too close. Looking back at the traditional ads media, online ads have some factor to achieve such as informations, entertainment, credibility, economic, and the ads value. This research aims to figure out the impact of those fators to attitude towards online advertising (ATOA) and online behavior (OB) at the millenias. Using SMART PLS 3.0, 100 respondents results that ATOA is not influenced by entertainment and the ads value. Animated and the millenias track record of browsing could be a consideration to the goal. Youtube is one of the spesific online media that could be used for the researches to find out more about the milllenias attitudes towards online advertising. Keywords: belief, attitude, advertising, millenia, online, behavior